2009
DOI: 10.1038/jp.2009.173
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of early parenteral nutrition for premature infants

Abstract: Objective: The objective of this study was to evaluate the safety and efficacy of early amino acid (early AA) administration in very low birth weight (VLBW) infants.Study Design: A pre-and post-intervention study was conducted after initiating an early AA administration protocol. Clinical outcomes were collected for all VLBW infants admitted on the first day of life for 9 months before protocol initiation (standard parenteral nutrition (PN)), and 10 months after initiation of early AA.Result: In all, 88 infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…In addition, Jadhav et al [14] demonstrated that any acidosis during early postnatal life occurs irrespective of dose and duration of parenteral amino acid administration. Multiple retrospective analyses [15][16][17][18][19][20][21][22][23][24] also have confirmed the beneficial effects described in the previous prospective studies. Most analyses were comparisons of epochs after nutritional policy had been changed.…”
Section: Parenteral Amino Acid Administration In Early Postnatal Phasesupporting
confidence: 84%
“…In addition, Jadhav et al [14] demonstrated that any acidosis during early postnatal life occurs irrespective of dose and duration of parenteral amino acid administration. Multiple retrospective analyses [15][16][17][18][19][20][21][22][23][24] also have confirmed the beneficial effects described in the previous prospective studies. Most analyses were comparisons of epochs after nutritional policy had been changed.…”
Section: Parenteral Amino Acid Administration In Early Postnatal Phasesupporting
confidence: 84%
“…Of available studies reporting duration of parenteral nutrition exposure, they typically involve interventions to supplement TPN formulations with additional nutrients or to standardize the approach to nutrition in low birth weight infants; for the purpose of comparison to our cases, we utilized data from control or standard care infants within these studies. Infants from these studies had similar birth weights to our cases and TPN exposure was variable across studies, with some showing very similar exposure to our cases and some with shorter duration of exposure . Similar to the diagnostic imaging data, these similarities and differences may reflect differences in practice across sites or may be reflective of the influence of the interventional trials they were a part of; whatever the case, our low birth weight hepatoblastoma cases appear to fall within the typical range for TPN exposure in the low birth weight neonatal population.…”
Section: Resultssupporting
confidence: 68%
“…Thus we are unable to make direct comparisons of our data with that previously reported. Relevant data regarding TPN exposure in neonates was also identified and is presented in Table . Of available studies reporting duration of parenteral nutrition exposure, they typically involve interventions to supplement TPN formulations with additional nutrients or to standardize the approach to nutrition in low birth weight infants; for the purpose of comparison to our cases, we utilized data from control or standard care infants within these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from individual amino acid supplementation, the administration of AA in parenteral nutrition (PN) has additionally been studied. In a comparative pre‐ and postintervention study, 47 early AA administration was associated with an increased incidence of surgical NEC in VLBW infants. Last, fatty acid supplementation was evaluated in one RCT 48 ; this study demonstrated a slightly increased incidence of NEC (5.3% vs 2%) in long‐chain polyunsaturated fatty acid (LCPUFA)–supplemented (fat mixture containing linoleic, α‐linolenic, and γ‐linolenic acids) compared with nonsupplemented infants, although the difference between groups was not statistically significant.…”
Section: Practice Guidelines and Rationalesmentioning
confidence: 99%